2010
DOI: 10.1007/s13539-010-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle wasting in cachexia and sarcopenia: molecular pathophysiology and impact of exercise training

Abstract: Skeletal muscle is the most abundant tissue in the human body, and the maintenance of its mass is essential to ensure basic function as locomotion, strength and respiration. The decision to synthesize or to break down skeletal muscle proteins is regulated by a network of signaling pathways that transmit external stimuli to intracellular factors regulating gene transcription. The tightly regulated balance of muscle protein breakdown and synthesis is disturbed in several distinct myopathies, but also in two path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
204
0
21

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(229 citation statements)
references
References 152 publications
4
204
0
21
Order By: Relevance
“…Differences in equipment, assessment protocol, participant selection, primary outcomes, and the disease stage may be responsible for discrepancy between the two study results. It is known that the occurrence of cancer is related to alterations in the metabolism of nutrients and hormonal changes, which can result in cachexia and thus reduced muscle strength 17 . Additionally, in the presence of cancer, subclinical inflammation seems to participate in the mechanisms of muscle strength reduction 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in equipment, assessment protocol, participant selection, primary outcomes, and the disease stage may be responsible for discrepancy between the two study results. It is known that the occurrence of cancer is related to alterations in the metabolism of nutrients and hormonal changes, which can result in cachexia and thus reduced muscle strength 17 . Additionally, in the presence of cancer, subclinical inflammation seems to participate in the mechanisms of muscle strength reduction 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews on effects of physical exercise in patients with cachexia have been narrative and not been specific to cancer patients [20,21] or have mainly discussed biological and pathophysiological aspects of exercise on cachexia-related muscle wasting [22,23]. Existing systematic reviews and meta-analyses on the effects of physical exercise in cancer patients have evaluated multiple end-points both during and after anti-cancer treatment [5,49], and many have primarily focused on specific outcomes such as fatigue [1] and quality of life [3].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a small number of clinical studies have demonstrated the contribution of exercise to reduce or delay cachexia in patients with chronic diseases other than cancer [18,19]. Previous reviews on effects of physical exercise in patients with cachexia have been narrative and not specific to cancer patients [20,21], or have mainly discussed biological and pathophysiological effects of exercise on cachexiarelated muscle wasting [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative stress can promote an unbalance of proteins and enzymes that in terferes in the regulation of keyfactors for cellular ho meostasis. The release of ROS (reactive oxygen species) drives the muscle cells to a catabolic cycle that leads to muscle breakdown, and activates the biochemical pa thway of NFkB, directly interfering in the transcription of essential genes for cellular metabolism (1,33). Fur thermore, oxidative stress plays a key role in the poten tiation of abnormalities generated by DM, since hyper glycemia in the presence of free radicals can lead to autooxidation of glucose and protein glycation (34).…”
Section: Anaerobic Training Avoids Proteolysismentioning
confidence: 99%
“…Among va rious complications associated to diabetes development, diabetic must handle an elevated rate of protein break down, known as sarcopeny. This condition is defined as a noninduced degenerative loss of muscle fiber and, consequently, loss of strength, associated to oxidative stress and reactive oxygen species (ROS) release (1). As a consequence of this dysfunction in diabetics, the ubiquitinproteasome signaling pathway (UPS -Ubi quitinProteasome System) can play an essential role in catalyzing unfolded or unwelcome proteins, which are subsequently catalyzed by proteasome (2,3) consider ing that in pathological conditions such as DM, gene expression of proteins involved in the regulation of proteolytic processes is elevated, resulting in degrada tion of myofibrillar structures (4).…”
mentioning
confidence: 99%